Insulin secretion, insulin sensitivity, and hepatic insulin extraction in first-degree relatives of type 2 diabetic patients - Pimenta, W.P. [UNESP] (2003)
To identify early metabolic abnormalities in type 2 diabetes mellitus, we measured insulin secretion, sensitivity to insulin, and hepatic insulin extraction in 48 healthy normal glucose-tolerant Brazilians, first-degree relatives of type 2 diabetic patients (FH+). Each individual was matched for sex, age, weight, and body fat distribution with a person without history of type 2 diabetes (FH-). Both groups were submitted to a hyperglycemic clamp procedure (180 mg/dl). Insulin release was evaluated in its two phases. The first was calculated as the sum of plasma insulin at 2.5, 5.0, 7.5, and 10.0 min after the beginning of glucose infusion, and the second as the mean plasma insulin level in the third hour of the clamp procedure. Insulin sensitivity index (ISI) was the mean glucose infusion rate in the third hour of the clamp experiment divided by the mean plasma insulin concentration during the same period of time. Hepatic insulin extraction was determined under fasting conditions and in the third hour of the clamp procedure as the ratio between C-peptide and plasma insulin levels. FH+ individuals did not differ from FH- individuals in terms of the following parameters [median (range)]: a) first-phase insulin secretion, 174 (116-221) vs 207 (108-277) µU/ml, b) second-phase insulin secretion, 64 (41-86) vs 53 (37-83) µU/ml, and c) ISI, 14.8 (9.0-20.8) vs 16.8 (9.0-27.0) mg kg-1 min-1/µU ml-1. Hepatic insulin extraction in FH+ subjects was similar to that of FH- ones at basal conditions (median, 0.27 vs 0.27 ng/µU) and during glucose infusion (0.15 vs 0.15 ng/µU). Normal glucose-tolerant Brazilian FH+ individuals well-matched with FH- ones did not show defects of insulin secretion, insulin sensitivity, or hepatic insulin extraction as tested by hyperglycemic clamp procedures.